Foreword From Editor - 17th Edition: Empowering Stakeholders: Reinventing Dialogues and Collaborations - Yatmo, Yandi Andri; Paramita, Kristanti Dewi; Suryantini, Rini (UI Scholars Hub, 2025)
This edition of AJCE examines the various frameworks and dialogues between stakeholders within their community engagement programs that aim to activate the structures and systems of society. This issue comprises three research articles that highlight the importance of community involvement in supporting programs with diverse objectives, including nature protection, rural development, and learning aid initiatives. In addition, this issue features three case-based articles that aim to discuss how community programs generate different ways of responding to societal issues, creating space for reflection and collaboration. The contributors to this study came from diverse backgrounds and fields of study, including forestry, architecture, education, and agriculture, providing multiple perspectives on when and how community engagement becomes a necessary process in different contexts.